ICT for smart evaluation of vernacular architecture in a stilt-house village - Almeida, Filipa (2020)
Vernacular architecture typologies, such as wooden stilt-houses, have been threatened by the vulnerability to conservation status degradation. This problem is not an exception in Portugal, where the few remaining examples have been neglected, with the disappearance or abandonment of almost all buildings, damaging architectural and urban spatial features. This legacy is rapidly disappearing, weakening the European cultural map. This research presents the results from a smart evaluation method using an ICT (information and communication technology) platform designed for the smart evaluation of wooden stilt-houses, considering their conservation status. This platform was used in the ﬁve remaining stilthouse villages still existing in Portugal including about 90 buildings and 300 inhabitants, located along Tagus river banks. This article refers to one of these case studies, the village of Escaroupim, which was chosen because it is the most urban space in between all of them. On one hand, the results are an exhaustive survey of vernacular buildings, useful as guideline for spatial strategies and instruments to protect this legacy. On the other hand, it can be used in other similar wooden buildings, to check their conservation status and therefore to deﬁne best rehabilitation actions.